Signet ring cell carcinoma of rectum metastasizing to synchronous renal cell carcinoma: a case report - Blagica Krsteska; Rubens Jovanovic; Aleksandar Eftimov; Boro Ilievski; Dragan Hadzi-Mancev; Bujar Osmani; Slavica Kostadinova-Kunovska (BMC Part of Springer Nature, 2021)
Background Rectal signet ring cell carcinoma is a rare type of colorectal adenocarcinoma characterized by an aggressive biological behavior and poor prognosis. The co-occurrence of colorectal carcinoma and renal cell carcinoma (RCC) has found in many hundreds of patients, many of whom also have additional malignancies. Cancer to cancer metastasis is rare and an uncommon phenomenon in malignancy, especially at the time of initial diagnosis, suggesting a genetic susceptibility. Case presentation: We present the case of a 66-year-old Macedonian man with synchronous rectal signet ring cell carcinoma and RCC with tumor to tumor metastasis feature. He underwent a left nephrectomy and anterior rectal resection after complaining of constipation for 3–4 months and the appearance of synchronous tumors on the imaging studies. Morphology and immunohistochemical analysis of specimens from the RCC revealed signet ring cells identical to the rectal signet ring cell carcinoma. The next-generation sequencing study revealed mutations in TP53 and ERBB2, and microsatellite stable signet ring cell carcinoma was determined by deoxyribonucleic acid (DNA) sequencing. Conclusions: Cancer to cancer metastasis, although rare, needs to be considered in synchronous tumors. RCC, when diagnosed in multiple synchronous tumors, should be examined carefully. The paucity of reported cases indicates the need for advanced research in imaging methods for metastasis and new therapeutic approaches.